Chronic obstructive pulmonary disease and metabolic associated fatty liver disease: prevalence and clinical characteristics - Doan, Le Minh Hanh; Au, Nhat Huy; Le, Thuong Vu; Tran, Thi Khanh Tuong (Tạp chí Y Dược Huế, 2025)
Background: Metabolic-Associated Fatty Liver Disease (MAFLD) is affecting approximately 24% of individuals and potentially leading to cirrhosis and hepatocellular carcinoma. This study aims to assess the prevalence of MAFLD in chronic obstructive pulmonary disease (COPD) patients and analyze their clinical characteristics. Methods: This cross-sectional descriptive study involved 120 stable COPD patients, using FibroScan to detect fatty liver, applying the 2020 APASL criteria for MAFLD diagnosis. Results: The prevalence of MAFLD was 53.3%, with a mean age of 68.9 ± 8.1 years, predominantly male (89.2%). Patients with MAFLD had higher weight, waist circumference, and BMI compared to those without MAFLD (p<0.05). Smoking rates were high in both groups, while alcohol consumption was notably higher in the MAFLD group (70.3% vs. 50.0%, p=0.023). They also had higher rates of mMRC ≥2 (98.4% vs. 66.1%, p<0.001), higher mean CAT scores (19.9 ± 5.1 vs. 14.1 ± 5.2, p<0.001), and experienced more exacerbations (68.7% with ≥2 per year). They were more likely to belong to the E group of COPD (89.0% vs. 21.5%, p<0.001). They also had higher rates of using reliver and controller medications containing ICS; lower FVC, FEV1, FEF 25-75%, and PEF indices (p<0.05); and a higher proportion of patients in GOLD stages 3 and 4 (p=0.002). Nearly all COPD patients who had fatty liver detected by FibroScan (98.5%) also had metabolic factors qualifying them for a MAFLD diagnosis. Blood glucose, HbA1c, insulin, and HOMA-IR levels were significantly higher in the MAFLD group (p<0.05). Conclusion: MAFLD affects 53.3% of COPD patients. It’s associated with higher weight, waist circumference, BMI, alcohol use, and inhaled corticosteroids. COPD patients with MAFLD experience more severe respiratory symptoms, poorer lung function, and more frequent exacerbations.